Comparative study of single dose versus multiple doses of antibiotic prophylaxis in caesarean delivery - S., Prathima; C., Savitha; KK, Tejeswini; GS, Anitha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Women undergoing caesarean delivery (CD) are 5 to 20 fold greater risk of infection than women of vaginal delivery group. Infectious complications after CD are an important and substantial cause of maternal morbidity and increase in the hospital stay and cost of treatment. The objective was to compare the efficacy of intravenous single dose, less costly cefotaxime and more expensive triple drug regimen (ceftriaxone+gentamycin+metrogyl) for 5 post operative days, for prophylaxis in caesarean delivery. Methods: It is a prospective comparative study was undertaken on 300 subjects with 2 parallel treatment groups. Data were analyzed using Graphpad Instat 3 McIntosh software by Student’s t test, Mann–Whitney U test, the Chi-squared test or fisher’s exact test. Results: Comparatively narrow spectrum low cost cefotaxime is as effective as more expensive commonly used triple drug regimen with no significant difference of infectious morbidity. Conclusions: Less costly cefotaxime should be preferred compared to more costly triple drug regimen for prophylaxis at caesarean section.